You Are Not Alone: The Role of VR and Immersive Content in Social Impact Campaigns (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
This article focuses on the use of virtual reality (VR) in the context of “impact campaigns.” Distinct in many ways from publishing a project on a digital storefront, im- pact campaigns assume a more carefully designed experi- ence, starting with the exhibit itself. Rather than considering VR as an end in itself, my goal is to situate this unique type of mediated experience within a larger network of social activism. Key to this project is an understanding of the role documentary films have played within societal movements. By learning from the larger history of impact production, this article seeks to highlight some of the shortcomings with VR as it has been used until now in socially minded projects. By extension, my goal is also to emphasize the things VR creators can learn from impact producers to make sure their projects reach the right audiences and affect them accordingly.
Keywords: Virtual reality; Impact production; Documentary; Social change; Empathy